Seasonal morphotypes of Drosophila suzukii differ in key life‐history traits during and after a prolonged period of cold exposure. Issue 17 (11th August 2020) - Panel, Aurore D. C.; Pen, Ido; Pannebakker, Bart A.; Helsen, Herman H. M.; Wertheim, Bregje
Abstract: Seasonal polyphenism in Drosophila suzukii manifests itself in two discrete adult morphotypes, the "winter morph" (WM) and the "summer morph" (SM). These morphotypes are known to differ in thermal stress tolerance, and they co‐occur during parts of the year. In this study, we aimed to estimate morph‐specific survival and fecundity in laboratory settings simulating field conditions. We specifically analyzed how WM and SM D. suzukii differed in mortality and reproduction during and after a period of cold exposure resembling winter and spring conditions in temperate climates. The median lifespan of D. suzukii varied around 5 months for the WM flies and around 7 months for the SM flies. WM flies showed higher survival during the cold‐exposure period compared with SM flies, and especially SM males suffered high mortality under these conditions. In contrast, SM flies had lower mortality rates than WM flies under spring‐like conditions. Intriguingly, reproductive status (virgin or mated) did not impact the fly survival, either during the cold exposure or during spring‐like conditions. Even though the reproductive potential of WM flies was greatly reduced compared with SM flies, both WM and SM females that had mated before the cold exposure were able to continuously produce viable offspring for 5 months under spring‐like conditions. Finally, the fertility of the overwintered WM males was almost zero, while the surviving SM males did not suffer reduced fertility. Combined with other studies on D. suzukii monitoring and overwintering behavior, these results suggest that overwintered flies of both morphotypes could live long enough to infest the first commercial crops of the season. The high mortality of SM males and the low fertility of WM males after prolonged cold exposure also highlight the necessity for females to store sperm over winter to be able to start reproducing early in the following spring. Abstract : Seasonal polyphenism in Drosophila suzukii manifests itself in two discrete adult morphotypes, the "winter morph" (WM) and the "summer morph" (SM). These morphotypes are known to differ in thermal stress tolerance, and they co‐occur during parts of the year. In this study, we aimed to estimate morph‐specific survival and fecundity in laboratory settings simulating field conditions.